2023
DOI: 10.1021/acs.iecr.3c01272
|View full text |Cite
|
Sign up to set email alerts
|

CFD-PBE Simulation of para-Xylene Crystallization Behavior and Process Amplification under Different Operating Conditions

Jiayu Dong,
Yinglong Wu,
Xuanchen Liu
et al.

Abstract: The crystallization technology is one of the most potential ways to produce para-xylene (PX) with high purity, but it has some drawbacks such as low yield and difficult to control crystallization due to the insufficient study of the PX nucleation characteristics and growth behavior. To further investigate this issue, this paper couples the Euler−Euler model and population balance equation (PBE) model, correlates the PX crystallization kinetics, and accurately solves the PBE using the Gaussian integral hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Mixing and stirring play a pivotal role in numerous industrial processing operations, including metallurgical refinement, pharmaceutical production, food processing, chemical manufacturing, and more. Simultaneously, mixing processes hold a prominent position in various scientific applications such as biochemical reactions, cell culture, and microbiology. The shape and volume of the mixing vessels significantly influence the mixing efficiency, determining the maximum production capacity of the equipment. Upscaling is an inevitable trend in the development of novel mixing apparatus …”
Section: Introductionmentioning
confidence: 99%
“…Mixing and stirring play a pivotal role in numerous industrial processing operations, including metallurgical refinement, pharmaceutical production, food processing, chemical manufacturing, and more. Simultaneously, mixing processes hold a prominent position in various scientific applications such as biochemical reactions, cell culture, and microbiology. The shape and volume of the mixing vessels significantly influence the mixing efficiency, determining the maximum production capacity of the equipment. Upscaling is an inevitable trend in the development of novel mixing apparatus …”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that the optimization method coupled with RSM and MOGA has been widely used in the design and optimization of heat exchangers. Thianpong et al used the grouped method of data handling (GMDH) models and the nondominated sorted genetic algorithm-II (NSGA-II) to optimize the hydrothermal performance of heat exchange tubes with rotors, and obtained the optimal boundary of experimental data according to the minimum friction coefficient and maximum Nusselt number. Wang et al adopted RSM combined with MOGA to optimize the structure of shell-and-tube heat exchangers.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation models typically consist of computational fluid dynamics (CFD) coupled with population balance equations (PBEs) in order to properly capture crystal size distribution (see e.g. 17 , 18 for recent examples of CFD-PBE crystallization modeling). Here, those studies focusing on anti-solvent crystallization, preferably of lovastatin and in jet crystallizers, are considered.…”
Section: Introductionmentioning
confidence: 99%